Ansatz einer handlungs- und entwicklungsorientierten Didaktik. Theoretische Grundlagen, empirische Bezüge und praktische Relevanz - Tulodziecki, G.; Grafe, S.; Herzig, Bardo (Jahrbuch für Allgemeine Didaktik 2013. Thementeil Neuere Ansätze in der Allgemeinen Didaktik)

"Irgendwie hängt doch alles mit allem zusammen." - Reflexion allgemeiner Unterrichtsprinzipien mit drehbuchbasierten Unterrichtsvideos im Lehramtsstudium - Nicolas, M.; Herzig, Bardo (Seminar - Lehrerbildung und Schule 2/2013)

Medien in der Schule - Herzig, Bardo (Handbuch Kinder und Medien)

Grundlagen medienbezogener Schulentwicklung - Herzig, Bardo; Klar, T.-M. (Lernende Schule - Medienkompetenz entwickeln 64/2013)

Gestaltungsorientierte Bildungsforschung und Didaktik. Theorie - Empirie - Praxis - Tulodziecki, G.; Grafe, S.; Herzig, Bardo

Medienbildung in der Schule. Konzepte, Strategien und Herausforderungen - Herzig, Bardo (Schulmagazin 5-10, 3/2013)

Bildungsstandards in der Medienbildung in internationaler Sicht - Herzig, Bardo; Grafe, S. (Medienimpulse, 47(1))

Rezension zu Paul Virilio: L’inertie polaire 1990/Rasender Stillstand 1997 - Alpsancar, Suzana (Nachdenken über Technik)

Propheten in die Schule? Einige Anmerkungen aus erziehungswissenschaftlicher Perspektive - Freitag, Christine (Prophetie in Islam und Christentum. Beiträge zur Komparativen Theologie)

Gesundheit als Merkmal ganzheitlicher Persönlichkeitsförderung im Mentorenprojekt Balu und Du - Freitag, Christine; Müller-Kohlenberg, H.; Drexler, S.; Rölker, S. (Soziale Arbeit – Forschung – Gesundheit. Forschung: bio-psycho-sozial)

Wie Lehrkräfte über die Religion ihrer Schüler und Schülerinnen denken - Freitag, Christine; Tegeler, E.; Bohnhorst, J. (Informationes Theologiae Europae, Internationales ökumenisches Jahrbuch für Theologie, 17. Jahrgang 2008-2013)

Musik als missionspädagogisches Instrument - Freitag, Christine (Musik in Religion – Religion in Musik)

Liquid Structure and Cluster Formation in Ionic Liquid/Water Mixtures – An Extensive ab initio Molecular Dynamics Study on 1-Ethyl-3-Methylimidazolium Acetate/Water Mixtures – Part 2 - Brehm, Martin; Weber, H.; Pensado, A. S.; Stark, A.; Kirchner, B. (Z. Phys. Chem.)

Understanding the Evaporation of Ionic Liquids using the Example of 1-Ethyl-3-Methylimidazolium Ethylsulfate - Malberg, F.; Brehm, Martin; Hollóczki, O.; Pensado, A. S.; Kirchner, B. (Phys. Chem. Chem. Phys.)

Carbene Formation in Ionic Liquids: Spontaneous, Induced, or Prohibited? - Hollóczki, O.; Firaha, D. S.; Friedrich, J.; Brehm, Martin; Cybik, R.; Wild, M.; Stark, A.; Kirchner, B. (J. Phys. Chem. B)

Computing Vibrational Spectra from ab initio Molecular Dynamics - Thomas, M.; Brehm, Martin; Fligg, R.; Vöhringer, P.; Kirchner, B. (Phys. Chem. Chem. Phys.)

Beobachterbericht zum Forum: Wie abgeschlossen ist die Prophetie? Prophetische Ansprüche nach Jesus Christus und Muhammad - Tatari, Muna (Die Boten Gottes. Prophetie in Christentum und Islam)

Trinität - Anstoß für das islamisch-christliche Gespräch

On Taqlīd: Ibn al Qayyim’s Critique of Authority in Islamic Law - Mustafa, Abdul Rahman

Professional knowledge of physics student teachers – ProfiLe-P - Riese, Josef; Borowski, Andreas; Fischer, Hans E.; Gramzow, Yvonne; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst; Tomczyszyn, Elisabeth; Walzer, Martin (KoKoHs Working Papers 3)

Fachwissen Physik – Innere Struktur und Faktoren des Wissenserwerbs - Woitkowski, David; Riese, Josef; Reinhold, Peter (Inquiry-based Learning – Forschendes Lernen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Hannover 2012)

Wirksamkeit der Physiklehrerausbildung in Österreich - Krumphals, Ingrid; Riese, Josef; Hopf, Martin; Reinhold, Peter (Inquiry-based Learning – Forschendes Lernen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Hannover 2012)

Electronic signature of the instantaneous asymmetry in the first coordination shell of liquid water - Kühne, Thomas D.; Khaliullin, Rustam Z. (Nature Commun.)

Selbstbezogene Facetten und Anerkennungs- bzw. Missachtungserfahrungen im Sportunterricht - Grimminger-Seidensticker, Elke (Sportpädagogik zwischen Stillstand und Beliebigkeit)

Besondere Sichtbarkeit durch Unsichtbarkeit – Wie sich Schüler/innen untereinander grundlegende Anerkennung im Sportunterricht verweigern - Grimminger-Seidensticker, Elke (Zeitschrift für sportpädagogische Forschung)

Sport Motor Competencies and the Experience of Social Recognition among Peers in Physical Education – A Video-based Study - Grimminger-Seidensticker, Elke (Physical Education and Sport Pedagogy)

Szenen des Helfens zwischen Schüler/innen im Sportunterricht – Eine videobasierte Studie - Grimminger-Seidensticker, Elke (Unterrichtswissenschaft)

BS 1149.1 extensions for an online interconnect fault detection and recovery - Sadeghi-Kohan, Somayeh; Namaki-Shoushtari, Majid; Javaheri, Fatemeh; Navabi, Zainalabedin (2012 IEEE International Test Conference)

A new structure for interconnect offline testing - Sadeghi-Kohan, Somayeh; Keshavarz, Shahrzad; Zokaee, Farzaneh; Farahmandi, Farimah; Navabi, Zainalabedin (East-West Design & Test Symposium (EWDTS 2013))

Korrosionsverhalten binärer Magnesium-Zink-Legierungen in salzhaltigen Medien - Hoyer, Kay-Peter; Angrisani, Gian Luigi; Klose, Christian; Bach, Friedrich-Wilhelm; Hassel, Thomas (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Publishing and Interlinking the Global Health Observatory Dataset - Zaveri, Amrapali; Lehmann, Jens; Auer, Sören; M. Hassan, Mofeed; Sherif, Mohamed; Martin, Michael (Semantic Web Journal)
The improvement of public health is one of the main indicators for societal progress. Statistical data for monitoring public health is highly relevant for a number of sectors, such as research (e.g. in the life sciences or economy), policy making, health care, pharmaceutical industry, insurances etc. Such data is meanwhile available even on a global scale, e.g. in the Global Health Observatory (GHO) of the United Nations's World Health Organization (WHO). GHO comprises more than 50 different datasets, it covers all 198 WHO member countries and is updated as more recent or revised data becomes available or when there are changes to the methodology being used. However, this data is only accessible via complex spreadsheets and, therefore, queries over the 50 different datasets as well as combinations with other datasets are very tedious and require a significant amount of manual work. By making the data available as RDF, we lower the barrier for data re-use and integration. In this article, we describe the conversion and publication process as well as use cases, which can be implemented using the GHO data.
Keywords: 2013 MOLE group_aksw zaveri martin lehmann auer hassan sherif simba dice sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:lod2 lod2page peer-reviewed gho

Schulbegleitung an Förderschulen in Nordrhein-Westfalen: Ausgangslage, Studienkonzeption und erste Ergebnisse - Kißgen, R.; Franke, Sebastian; Ladinig, B.; Mays, D.; Carlitscheck, J. (Nachdruck aus: Empirische Sonderpädagogik)

Schulbegleitung an Förderschulen in Nordrhein-Westfalen: Ausgangslage, Studienkonzeption und erste Ergebnisse - Kißgen, R.; Franke, Sebastian; Ladinig, B.; Mays, D.; Carlitscheck, J. (Empirische Sonderpädagogik)

Inklusion und Lehrerrolle - Das Schulsystem im Wandel - Mays, D.; Ladinig, B.; Carlitscheck, J.; Franke, Sebastian; Kißgen, R. (Praxis Schule 5-10)

Handeln unter Druck - Methoden der Entschleunigung - Mays, D.; Ladinig, B.; Carlitscheck, J.; Franke, Sebastian; Kißgen, R. (Praxis Schule 5-10)

Tierquälerei als Symptom von Callous-Unemotional Traits bei inhaftierten Jungen und Mädchen - Sevecke, K.; Franke, Sebastian; Krischer, M.K. (Kindheit und Entwicklung)

Threat and normative appeals to reduce product returns in online retailing – An effective marketing practice? - Garnefeld, I.; Münkhoff, Eva; Raum, K. (42nd EMAC Annual Conference, Istanbul)

How to prolong a sales promotion – Ex-post time extension versus reframing - Münkhoff, Eva; Garnefeld, I.; Bruns, A. (42nd EMAC Annual Conference, Istanbul)

Umsatz- und Profitabilitätsauswirkungen industrieller Dienstleistungen - Münkhoff, Eva

Athletes and novices are differently capable to recognize feint and non-feint actions - Güldenpenning, Iris; Steinke, Andreas; Koester, Dirk; Schack, Thomas (Experimental Brain Research)

Unconscious, incongruent primes initiate invalid motor actions - Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Abstracts of the 55th Conference of Experimental Psychologists (TeaP))

Procrastination: When Good Things Don’t Come to Those Who Wait - Klingsieck, Katrin B. (European Psychologist)
Procrastination is a well-known phenomenon that often entails negative outcomes with regard to performance and subjective well-being. In an attempt to understand the (alarming) character of procrastination, a large body of research on the causes, correlates, and consequences of procrastination has been accumulating over the last 40 years. The aim of this paper is to provide a systematic characterization of the trends in procrastination research and to suggest future directions for research and practice. The systematic characterization comprises a comparison of procrastination to functional forms of delay (referred to as strategic delay) and a presentation of the theoretical approaches to explaining procrastination. The future directions suggested pertain to the development of a differentiated understanding of procrastination and of integral interventions.
Keywords: General Psychology; Arts and Humanities (miscellaneous)

Procrastination - Klingsieck, Katrin B.; Steel, Piers (Oxford Bibliographies in Psychology)

Procrastination in Different Life-Domains: Is Procrastination Domain Specific? - Klingsieck, Katrin B. (Current Psychology)
Keywords: General Psychology

Why Students Procrastinate: A Qualitative Approach - Klingsieck, Katrin B.; Grund, Axel; Schmid, Sebastian; Fries, Stefan (Journal of College Student Development)
Keywords: Education

Ich sehe was, was du nicht siehst–Die unbewusste Verarbeitung von Blicktäuschungen im Basketball - Güldenpenning, Iris; Schäfer, A; Selig, C; Schack, Thomas (Angewandte Sportpsychologie. 45. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Inkongruente, unbewusste Primes können Fehlhandlungen initiieren - Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Angewandte Sportpsychologie. 45. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Model based enhancement of an autonomous system with a piezoelectric harvester - Al-Ashtari, Waleed
''Energy Harvester`` wandeln Umgebungsenergie in nützliche elektrische Energie. Zur Berechnung der elektromechanischen Charakteristik eines piezoelektrischen ''Energy Harvesters" wird ein auf Materialeigenschaften, Geometrie und Randbedingungen basierendes analytisches Modell vorgestellt. Dieses dient als Basis für ein weiteres Modell, welches den Betrieb eines autonomen Systems beschreibt. Die theoretischen Arbeiten werden mit Laborversuchen validiert. Es zeigt sich, dass der piezoelektrische Harvester im eingeschwungenen Zustand durch den Gleichrichtungsvorgang zwei abwechselnde Lastzustände erfährt. Dies führt zu nichtlinearem Verhalten des Harvesters, besonders wenn die angeschlossene Last eine geringe Impedanz hat. Desweiteren zeigen die Ergebnisse, dass ein solches autonomes System effizient arbeitet, wenn es an eine Last mit hoher Impedanz angeschlossen ist und bei einer der Antiresonanzfrequenz des piezoelektrischen Harvesters entsprechenden Frequenz angeregt wird.Das Modell des autonomen Systems wird auf ein System mit mehreren piezoelektrischen Wandlern erweitert. Zur praktischen Implementierung eines solchen Systems wird eine Technik zur Frequenzeinstellung eingeführt, da die optimalen Betriebsfrequenzen der einzelnen Wandler aufeinander abgestimmt werden müssen. Die Einstellung erfolgt, indem die Entfernung zwischen zwei Permanentmagneten und damit deren Anziehungskraft, welche die Steifigkeit des Harvesters beeinflusst, angepasst wird. Diese Technik zur Frequenzeinstellung wird modelliert und experimentell validiert. Die Ergebnisse zeigen, dass die Frequenzeinstellung mittels Permanentmagneten eine einfache und zugleich effektive Lösung für das Problem der Frequenzanpassung piezoelektrischer ''Energy Harvester" darstellt. Energy harvesters convert ambient energy into useful electrical energy. An analytical model for calculating the electromechanical characteristics of a piezoelectric harvester based on the material properties, geometry and boundary conditions is presented. This model is the basis for a further model which describes the operation of an autonomous system powered by a piezoelectric harvester. This theoretical work is validated by corresponding laboratory experiments. It is found that, in steady-state operation, the piezoelectric harvester experiences two alternating load conditions due to the rectification process. These load conditions make the system behave nonlinearly, especially if the connected electrical load is of low impedance. Furthermore, the results show that such an autonomous system works efficiently if it is connected to a high impedance load and excited at a frequency matching the anti-resonance frequency of the piezoelectric harvester.The model of an autonomous system is extended to describe a system with multiple piezoelectric transducers. For implementing such a system, the optimum operation frequencies of the individual transducers must be adjusted. Therefore, a frequency tuning method is introduced. The tuning is accomplished by adjusting the distance between two permanent magnets and thus changing the attracting force between them in order to affect the structural stiffness of the harvester. This tuning method is modeled and validated experimentally. The results show that frequency tuning using permanent magnets is a simple and effective solution for the frequency adjustment of piezoelectric energy harvesters.

Struktur eines Instruments zur Kompetenzerfassung in der Sportlehrerausbildung. - Kehne, Miriam; Seifert, Andreas; Schaper, Niclas (Sportunterricht)

Gesundheit von Lehramtsstudierenden: ausgewählte Ergebnisse einer empirischen Untersuchung an der Universität Paderborn - Brandl-Bredenbeck, Hans-Peter; Kämpfe, Astrid; Köster, Carolin (Gesundheitsförderung im Setting Schule)

Studium heute - gesundheitsfördernd oder gesundheitsgefährdend?: eine Lebensstilanalyse - Brandl-Bredenbeck, Hans-Peter; Kämpfe, Astrid; Köster, Carolin

Syntactic perspectives on directive speech acts : a contrastive study - Freudinger, Markus
This thesis is situated in the field of contrastive pragmatics and compares the syntactic realizations of equivalent directive speech acts in English and German. The term directive speech act is being used in a more narrow sense than intended by Searle (1975).Dramatic plays are used as data source for the original language and the translation into the other language. The four texts are Brechts “Mutter Courage und Ihre Kinder“, Dürrenmatts „Die Physiker“, Osbornes „Look Back in Anger“, and Leighs „Abigail‘s Party“.The central questions of this study are: Which forms are available in each language? Which specific function does a form fulfill in the system of each language? How do forms correspond across languages?In general, realizations as regular sentences, irregular sentences and non-sentences are possible. In the case of regular sentences, the subcategories imperative, declarative, yes-no interrogative, and wh-interrogative are possible in both languages. German also offers the adhortative and the infinitive. There are remarkable differences in terms of frequencies for these types.In general, German and English behave rather similar in their use of the clause types. The detailed qualitative description of specific examples constitutes the main part of the analysis and answers the following questions: which forms occur as equivalences? Under which conditions can declaratives and interrogatives be used directively?Non-sentences also play an important role. Formal categories, however, are not helpful; hence the utterances were grouped according to functional aspects. These are: propositional content, relationship between speaker and hearer, and illocutionary force.

FPGA-accelerated Key Search for Cold-Boot Attacks against AES - Riebler, Heinrich; Kenter, Tobias; Sorge, Christoph; Plessl, Christian (Proceedings of the International Conference on Field-Programmable Technology (FPT))
Cold-boot attacks exploit the fact that DRAM contents are not immediately lost when a PC is powered off. Instead the contents decay rather slowly, in particular if the DRAM chips are cooled to low temperatures. This effect opens an attack vector on cryptographic applications that keep decrypted keys in DRAM. An attacker with access to the target computer can reboot it or remove the RAM modules and quickly copy the RAM contents to non-volatile memory. By exploiting the known cryptographic structure of the cipher and layout of the key data in memory, in our application an AES key schedule with redundancy, the resulting memory image can be searched for sections that could correspond to decayed cryptographic keys; then, the attacker can attempt to reconstruct the original key. However, the runtime of these algorithms grows rapidly with increasing memory image size, error rate and complexity of the bit error model, which limits the practicability of the approach.In this work, we study how the algorithm for key search can be accelerated with custom computing machines. We present an FPGA-based architecture on a Maxeler dataflow computing system that outperforms a software implementation up to 205x, which significantly improves the practicability of cold-attacks against AES.
Keywords: coldboot

On-The-Fly Computing: A Novel Paradigm for Individualized IT Services - Happe, Markus; Kling, Peter; Plessl, Christian; Platzner, Marco; Meyer auf der Heide, Friedhelm (Proceedings of the 9th IEEE Workshop on Software Technology for Future embedded and Ubiquitous Systems (SEUS))
In this paper we introduce “On-The-Fly Computing”, our vision of future IT services that will be provided by assembling modular software components available on world-wide markets. After suitable components have been found, they are automatically integrated, configured and brought to execution in an On-The-Fly Compute Center. We envision that these future compute centers will continue to leverage three current trends in large scale computing which are an increasing amount of parallel processing, a trend to use heterogeneous computing resources, and—in the light of rising energy cost—energy-efficiency as a primary goal in the design and operation of computing systems. In this paper, we point out three research challenges and our current work in these areas.

Parallel Macro Pipelining on the Intel SCC Many-Core Computer - Suess, Tim; Schoenrock, Andrew; Meisner, Sebastian; Plessl, Christian (Proc. Int. Symp. on Parallel and Distributed Processing Workshops (IPDPSW))

The Localization of Carbon Markets: Negotiated Ambiguity - Anita, Engels; Knoll, Lisa (Global Themes and Local Variations in Organization and Management. Perspectives on Glocalization)

Justification, conventions, and institutions in economic fields - Knoll, Lisa (economic sociology_the european electronic newsletter)

Zeitschrift für Medienwissenschaft 9: Themenschwerpunkt Werbung

Die Masse und der Automat als Metapher und Modell - Bartz, Christina (Automatismen – Selbst-Technologien)

Vibrational Fingerprints of LiNbO3-LiTaO3Mixed Crystals - Sanna, Simone; Riefer, A.; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Rüsing, Michael; Widhalm, A.; Zrenner, Artur (Ferroelectrics)
Atomistic simulations in the framework of the density functional theory have been used to model morphologic and vibrational properties of lithium niobate–lithium tantalate mixed crystals as a function of the [Nb]/[Ta] ratio. Structural parameters such as the crystal volume and the lattice parameters a and c vary roughly linearly from LiTaO3 to LiNbO3, showing only minor deviations from the Vegard behavior. Our ab initio calculations demonstrate that the TO1, TO2 and TO4 vibrational modes become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. Furthermore, the investigated zone center A1 -TO phonon modes are characterized by a pronounced stoichiometry dependence. Frequency shifts as large as 30 cm−1 are expected as the [Nb]/[Ta] ratio grows from 0 to 1. Therefore, spectroscopic techniques sensitive to the A1 modes (such as Raman spectroscopy), can be employed for a direct and non-destructive determination of the crystal composition.
Keywords: Ferroelectrics; vibrational properties; LiNbO3; LiTaO3; mixed crystals

Transition energies and direct-indirect band gap crossing in zinc-blende AlxGa1−xN - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schupp, Thorsten; As, Donat J.; Feneberg, Martin; Goldhahn, Rüdiger (Physical Review B)

Texte zur Theorie des Pop

ShePOP - Frauen. Macht. Musik!

DoA-Based Microphone Array Position Self-Calibration Using Circular Statistic - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2013))
In this paper we propose an approach to retrieve the absolute geometry of an acoustic sensor network, consisting of spatially distributed microphone arrays, from reverberant speech input. The calibration relies on direction of arrival measurements of the individual arrays. The proposed calibration algorithm is derived from a maximum-likelihood approach employing circular statistics. Since a sensor node consists of a microphone array with known intra-array geometry, we are able to obtain an absolute geometry estimate, including angles and distances. Simulation results demonstrate the effectiveness of the approach.
Keywords: Geometry calibration; microphone arrays; position self-calibration

Sampling Rate Synchronisation in Acoustic Sensor Networks with a Pre-Trained Clock Skew Error Model - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (21th European Signal Processing Conference (EUSIPCO 2013))
In this paper we present a combined hardware/software approach for synchronizing the sampling clocks of an acoustic sensor network. A first clock frequency offset estimate is obtained by a time stamp exchange protocol with a low data rate and computational requirements. The estimate is then postprocessed by a Kalman filter which exploits the specific properties of the statistics of the frequency offset estimation error. In long term experiments the deviation between the sampling oscillators of two sensor nodes never exceeded half a sample with a wired and with a wireless link between the nodes. The achieved precision enables the estimation of time difference of arrival values across different hardware devices without sharing a common sampling hardware.
Keywords: synchronization; acoustic sensor network

Effects of model orientation on the visuomotor imitation of arm movements: The role of mental rotation - Krause, Daniel; Kobow, Sven (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Grundlagen der Bewegungswissenschaft und -lehre - Olivier, Norbert; Rockmann, Ulrike; Krause, Daniel

“The Space of Culture. Outlines of a Transcendental Philosophy of Culture Following the Marburg School of Neo-Kantianism (Cohen, Natorp, and Cassirer) - Luft, Sebastian

IT-gestützte Ausbildung von Feuerwehr - Führungskräften und -stäben: Zwischen virtueller Lage und realer Erfahrung - Pottebaum, Jens; Marterer, Robin; Koch, Rainer (Entscheiden in kritischen Situationen)

Rezension von: Jens Dreßler: Vom Sinn des Lernens an der Geschichte. Historische Bildung in schultheoretischer Sicht, Stuttgart: Kohlhammer, 2012 - Hartung, Olaf (Das Historisch-Politische Buch)

schwarzweiss-vier

"Gung Ho": Nationale Kultur und Schlanke Produktion in Ron Howards Spielfilm. - Schneider, Martin (Macht und Employment Relations)

Theodor Fontanes ›Frauenromane‹ »Cécile« und »Effi Briest« im historischen Publikationskontext - Gretz, Daniela (Zeitschriftenliteratur/Fortsetzungsliteratur)

»Weißer Fleck« und »dunkler Kontinent«. Afrika-Bilder seit dem 19. Jahrhundert - Gretz, Daniela (Themen Thesen Texte. Magazin des Exzellenzclusters ›Kulturelle Grundlagen von Integration‹)

Professor Bienlein erfindet das Medium seiner Träume - Bartz, Christina (Das Medium meiner Träume. Hartmut Winkler zum 60. Geburtstag)

Attack-test and verification systems, steps towards verifiable anomaly detection - Fourné, Marcel; Petersen, Dominique; Pohlmann, Norbert (INFORMATIK 2013 – Informatik angepasst an Mensch, Organisation und Umwelt)

CuO and Co3O4 Nanoparticles: Synthesis, Characterizations, and Raman Spectroscopy - Rashad, M.; Rüsing, Michael; Berth, Gerhard; Lischka, K.; Pawlis, A. (Journal of Nanomaterials)
Copper oxide and cobalt oxide (CuO, Co3O4) nanocrystals (NCs) have been successfully prepared in a short time using microwave irradiation without any postannealing treatment. Both kinds of nanocrystals (NCs) have been prepared using copper nitrate and cobalt nitrate as the starting materials and distilled water as the solvent. The resulted powders of nanocrystals (NCs) were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and atomic force microscopy (AFM) measurements. The obtained results confirm the presence of the both of oxides nanopowders produced during chemical precipitation using microwave irradiation. A strong emission under UV excitation is obtained from the prepared CuO and Co3O4 nanoparticles. The results show that the nanoparticles have high dispersion and narrow size distribution. The line scans of atomic force microscopy (AFM) images of the nanocrystals (NCs) sprayed on GaAs substrates confirm the results of both X-ray diffraction and transmission electron microscopy. Furthermore, vibrational studies have been carried out using Raman spectroscopic technique. Specific Raman peaks have been observed in the CuO and Co3O4 nanostructures, and the full width at half maximum (FWHM) of the peaks indicates a small particle size of the nanocrystals.
Keywords: General Materials Science

The Directed Search Method for Pareto Front Approximations with Maximum Dominated Hypervolume - Sosa, Hernández V; Schütze, O; Rudolph, G; Trautmann, Heike (EVOLVE — A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation IV)
In many applications one is faced with the problem that multiple objectives have to be optimized at the same time. Since typically the solution set of such multi-objective optimization problems forms a manifold which cannot be computed analytically, one is in many cases interested in a suitable finite size approximation of this set. One widely used approach is to find a representative set that maximizes the dominated hypervolume that is defined by the images in objective space of these solutions and a given reference point. In this paper, we propose a new point-wise iterative search procedure, Hypervolume Directed Search (HVDS), that aims to increase the hypervolume of a given point in an archive for bi-objective unconstrained optimization problems. We present the HVDS both as a standalone algorithm and as a local searcher within a specialized evolutionary algorithm. Numerical results confirm the strength of the novel approach.

Finding Evenly Spaced Pareto Fronts for Three-Objective Optimization Problems - Trautmann, Heike; Rudolph, G; Dominguez-Medina, C; Schütze, O (EVOLVE — A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation II)
The averaged Hausdorff distance Δ p is a performance indicator in multi-objective evolutionary optimization which simultaneously takes into account proximity to the true Pareto front and uniform spread of solutions. Recently, the multi-objective evolutionary algorithm Δ p -EMOA was introduced which successfully generates evenly spaced Pareto front approximations for bi-objective problems by integrating an external archiving strategy into the SMS-EMOA based on Δ p . In this work a conceptual generalization of the Δ p -EMOA for higher objective space dimensions is presented and experimentally compared to state-of-the art EMOA as well as specialized EMOA variants on three-dimensional optimization problems.

A Feature-Based Comparison of Local Search and the Christofides Algorithm for the Travelling Salesperson Problem - Nallaperuma, Samadhi; Wagner, Markus; Neumann, Frank; Bischl, Bernd; Mersmann, Olaf; Trautmann, Heike (Proceedings of the Twelfth Workshop on Foundations of Genetic Algorithms XII)
Understanding the behaviour of well-known algorithms for classical NP-hard optimisation problems is still a difficult task. With this paper, we contribute to this research direction and carry out a feature based comparison of local search and the well-known Christofides approximation algorithm for the Traveling Salesperson Problem. We use an evolutionary algorithm approach to construct easy and hard instances for the Christofides algorithm, where we measure hardness in terms of approximation ratio. Our results point out important features and lead to hard and easy instances for this famous algorithm. Furthermore, our cross-comparison gives new insights on the complementary benefits of the different approaches.
Keywords: approximation algorithms; local search; traveling salesperson problem; feature selection; prediction; classification

Evenly Spaced Pareto Front Approximations for Tricriteria Problems Based on Triangulation - Rudolph, G; Trautmann, Heike; Sengupta, S; Schütze, O (Evolutionary Multi-Criterion Optimization — 7$^th$ International Conference, EMO 2013, Sheffield, UK, Proceedings)
In some technical applications like multiobjective online control an evenly spaced approximation of the Pareto front is desired. Since standard evolutionary multiobjective optimization (EMO) algorithms have not been designed for that kind of approximation we propose an archive-based plug-in method that builds an evenly spaced approximation using averaged Hausdorff measure between archive and reference front. In case of three objectives this reference font is constructed from a triangulated approximation of the Pareto front from a previous experiment. The plug-in can be deployed in online or offline mode for any kind of EMO algorithm.

Directed Search Method for Indicator-based Multi-objective Evolutionary Algorithms - Sosa-Hernandez, VA; Schütze, O; Rudoph, G; Trautmann, Heike (Proceeding of the Fifteenth Annual Conference Companion on Genetic and Evolutionary Computation Conference Companion)
Indicator based evolutionary algorithms have caught the interest of many researchers for the treatment of multi-objective optimization problems in the recent past since they deliver the desired approximation of the solution set and due to a usually better performance compared to dominance based algorithms. Nevertheless, these methods still suffer the drawback that many function evaluations are required to obtain a suitable representation of the solution set. The aim of this study is to present the Directed Search (DS) Method as local searcher within global indicator based optimization algorithms. For this, we will present the DS in the context of hypervolume maximization leading to both a new local search algorithm and a new memetic algorithm. Further, we will present first attempts to adapt the DS to a class of parameter dependent problems.

Evenly spaced Pareto fronts of quad-objective problems using PSA partitioning technique - Dominguez-Medina, C; Rudolph, G; Schütze, O; Trautmann, Heike (Proceedings of the 2013 IEEE Congress on Evolutionary Computation (CEC))
Here we address the problem of computing finite size Hausdorff approximations of the Pareto front of four-objective optimization problems by means of evolutionary computing. Since many applications desire an approximation evenly spread along the Pareto front and approximations that are good in the Hausdorff sense are typically evenly spread along the Pareto front we consider three different evolutionary multi-objective algorithms tailored to that purpose, where two of them are based on the Part and Selection Algorithm (PSA). Finally, we present some numerical results indicating the strength of the novel methods.

Reactive strategy choice in StarCraft by means of Fuzzy Control - Preuss, Mike; Kozakowski, Daniel; Hagelbäck, Johan; Trautmann, Heike (2013 IEEE Conference on Computational Inteligence in Games (CIG))
Current StarCraft bots are not very flexible in their strategy choice, most of them just follow a manually optimized one, usually a rush. We suggest a method of augmenting existing bots via Fuzzy Control in order to make them react on the current game situation. According to the available information, the best matching of a pool of strategies is chosen. While the method is very general and can be applied easily to many bots, we implement it for the existing BTHAI bot and show experimentally how the modifications affects its gameplay, and how it is improved compared to the original version.

Indicator-based Selection in Evolutionary Multiobjective Optimization Algorithms Based On the Desirability Index - Trautmann, Heike; Wagner, T; Biermann, D; Weihs, C (Journal of Multi-Criteria Decision Analysis)
In multiobjective optimization, the identification of practically relevant solutions on the Pareto-optimal front is an important research topic. Desirability functions (DFs) allow the preferences of the decision maker to be specified in an intuitive way. Recently, it has been shown for continuous optimization problems that an a priori transformation of the objectives by means of DFs can be used to focus the search of a hypervolume-based evolutionary algorithm on the desired part of the front. In many-objective optimization, however, the computational complexity of the hypervolume can become a crucial part. Thus, an alternative to this approach will be presented in this paper. The new algorithm operates in the untransformed objective space, but the desirability index (DI), that is, a DF-based scalarization, will be used as the second-level selection criterion in the non-dominated sorting. The diversity and uniform distribution of the resulting approximation are ensured by the use of an external archive. In the experiments, different preferences are specified as DFs, and their effects are investigated. It is shown that trade-off solutions are generated in the desired regions of the Pareto-optimal front and with a density adaptive to the DI. The efficiency of the approach with respect to increasing objective space dimension is also analysed using scalable test functions. The convergence speed is superior to other set-based and preference-based evolutionary multiobjective algorithms while the approach is of low computational complexity due to cheap DI evaluations. Copyright © 2013 John Wiley & Sons, Ltd.

Preference Articulation by Means of the R2 Indicator - Wagner, Tobias; Trautmann, Heike; Brockhoff, Dimo (Evolutionary Multi-Criterion Optimization)
In multi-objective optimization, set-based performance indicators have become the state of the art for assessing the quality of Pareto front approximations. As a consequence, they are also more and more used within the design of multi-objective optimization algorithms. The R2 and the Hypervolume (HV) indicator represent two popular examples. In order to understand the behavior and the approximations preferred by these indicators and algorithms, a comprehensive knowledge of the indicator’s properties is required. Whereas this knowledge is available for the HV, we presented a first approach in this direction for the R2 indicator just recently. In this paper, we build upon this knowledge and enhance the considerations with respect to the integration of preferences into the R2 indicator. More specifically, we analyze the effect of the reference point, the domain of the weights, and the distribution of weight vectors on the optimization of $μ$ solutions with respect to the R2 indicator. By means of theoretical findings and empirical evidence, we show the potentials of these three possibilities using the optimal distribution of $μ$ solutions for exemplary setups.

R2-EMOA: Focused Multiobjective Search Using R2-Indicator-Based Selection - Trautmann, Heike; Wagner, Tobias; Brockhoff, Dimo (Learning and Intelligent Optimization)
An indicator-based evolutionary multiobjective optimization algorithm (EMOA) is introduced which incorporates the contribution to the unary R2-indicator as the secondary selection criterion. First experiments indicate that the R2-EMOA accurately approximates the Pareto front of the considered continuous multiobjective optimization problems. Furthermore, decision makers’ preferences can be included by adjusting the weight vector distributions of the indicator which results in a focused search behavior.

A Novel Feature-Based Approach to Characterize Algorithm Performance for the Traveling Salesman Problem - Mersmann, O; Bischl, B; Trautmann, Heike; Wagner, M; Bossek, J; Neumann, F (Annals of Mathematics and Artificial Intelligence)
Meta-heuristics are frequently used to tackle NP-hard combinatorial optimization problems. With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesperson problem (TSP). Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.

Server based indoor navigation using RSSI and inertial sensor information - Hoang, Manh Kha; Schmitz, Sarah; Drueke, Christian; Vu, Dang Hai Tran; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Positioning Navigation and Communication (WPNC), 2013 10th Workshop on)
In this paper we present a system for indoor navigation based on received signal strength index information of Wireless-LAN access points and relative position estimates. The relative position information is gathered from inertial smartphone sensors using a step detection and an orientation estimate. Our map data is hosted on a server employing a map renderer and a SQL database. The database includes a complete multilevel office building, within which the user can navigate. During navigation, the client retrieves the position estimate from the server, together with the corresponding map tiles to visualize the user's position on the smartphone display.
Keywords: SQL; navigation; smart phones; wireless LAN; RSSI; SQL database; complete multilevel office building; inertial sensor information; inertial smartphone sensors; map renderer; received signal strength index information; relative position estimates; server based indoor navigation; step detection; wireless-LAN access points; Smartphone; fingerprint; indoor navigation; map tile

A Hidden Markov Model for Indoor User Tracking Based on WiFi Fingerprinting and Step Detection - Hoang, Manh Kha; Schmalenstroeer, Joerg; Drueke, Christian; Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (21th European Signal Processing Conference (EUSIPCO 2013))
In this paper we present a modified hidden Markov model (HMM) for the fusion of received signal strength index (RSSI) information of WiFi access points and relative position information which is obtained from the inertial sensors of a smartphone for indoor positioning. Since the states of the HMM represent the potential user locations, their number determines the quantization error introduced by discretizing the allowable user positions through the use of the HMM. To reduce this quantization error we introduce â??pseudoâ?? states, whose emission probability, which models the RSSI measurements at this location, is synthesized from those of the neighboring states of which a Gaussian emission probability has been estimated during the training phase. The experimental results demonstrate the effectiveness of this approach. By introducing on average two pseudo states per original HMM state the positioning error could be significantly reduced without increasing the training effort.

Pro forma earnings disclosure: the effects of non-GAAP earnings and earnings-before on investors’ information processing - Reimsbach, Daniel (Journal of Business Economics)
Keywords: Economics and Econometrics; Business and International Management

The Effects of Negative Incidents in Sustainability Reporting on Investors’ Judgments–an Experimental Study of Third‐party Versus Self‐disclosure in the Realm of Sustainable Development - Reimsbach, Daniel; Hahn, Rüdiger (Business Strategy and the Environment)
ABSTRACT This study examines how the disclosure of negative sustainability‐related incidents affects the investment‐related judgments of decision‐makers. Participants in a sequential 2 × 2 between‐subjects experiment first received a company's financial information before viewing additional sustainability information (by the company and by a non‐governmental organization (NGO); with and without negative disclosure). Results indicate that self‐reporting of negative incidents does not affect decision‐makers’ stock price estimates and investment decisions compared with judgments based on financial information only. However, third‐party disclosure of these incidents by a NGO has a negative affect on these investment‐related judgments. Furthermore, the magnitude of the NGO reporting effect depends on whether the company itself simultaneously reports these incidents. Thus, disclosing negative incidents in sustainability reporting could lose some of its apparent stigma. Instead of avoiding negative reporting altogether, managers might use it as a risk mitigation tool in their reporting strategy. The results also emphasize the power of the often‐mentioned ‘watchdog’ function of NGOs acting as stakeholder advocates. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

The Phenomenology of Intersubjectivity in Husserl and Jaspers: On the Capacities and Limits of Empathy and Communication in Psychiatric Praxis - Luft, Sebastian; Schlimme, Jann E (Psychopathology. International Journal of Descriptive and Experimental Psychopathology, Phenomenology and Psychiatric Diagnosis)

Paul Natorp: Allgemeine Psychologie nach kritischer Methode
Der heute fast in Vergessenheit geratene Philosoph und Pädagoge Paul Natorp (1854-1924) war einer der herausragenden Denker Deutschlands. Der philosophischen Bewegung der Marburger Schule des Neukantianismus entstammend, ist Natorp der Verfasser eines weit verzweigten Werkes auch jenseits der Philosophie. Mit seiner ›Allgemeinen Psychologie‹ gelang es ihm, eine Psychologie nach kritischer Methode zu begründen und gleichzeitig den Weg für die Phänomenologie zu bereiten. Führte der Neukantianismus längere Zeit in der Forschung eher ein Nischendasein, wird er mittlerweile wieder verstärkt wahrgenommen und hat seitdem beeindruckende Ergebnisse geliefert. Die Neuedition von Natorps ›Allgemeiner Psychologie‹ durch Sebastian Luft macht diesen wichtigen Text nun endlich wieder zugänglich. Eine ausführliche Einleitung stellt das Werk in seinen historischen Kontext, von Natorp nicht ausgewiesene Zitate und Anspielungen werden kenntlich gemacht und kommentiert.

Archiv Untergrund; Damage Report 1&2 - Schulze, Max (WG/3ZI/K/BAR. Ein Haus für Künstler, Gäste, Freunde)

Geschichte schreiben lernen: empirische Erkundungen zum konzeptionellen Schreibhandeln im Geschichtsunterricht - Hartung, Olaf

No Loitering - Schulze, Max (A World of Wild Doubt)

Pembaur, Kalt Maria - Höink, Dominik (Lexikon der Kirchenmusik)

Palestrinastil - Höink, Dominik (Lexikon der Kirchenmusik)

On the ecological validity of a password study - Fahl, Sascha; Harbach, Marian; Acar, Yasemin; Smith, Matthew (Proceedings of the Ninth Symposium on Usable Privacy and Security)